RANCANG BANGUN DAN EVALUASI AWAL SISTEM DIGITAL LAYANAN HUNIAN KAMPUS BERBASIS WEB DALAM MENDUKUNG EFISIENSI OPERASIONAL DAN KUALITAS LAYANAN PENDIDIKAN - Haryanti Yanti; Sri Mitrawati; Indraddin Indraddin; Reno Novita Sari (STKIP Pesisir Selatan, 2026)
Objective: This study aims to design and conduct an initial evaluation of a web-based digital campus residential service system at Andalas Residence, Universitas Andalas, as part of efforts to improve operational efficiency and educational support service quality in higher education. Methods: This applied research used a mixed-methods approach. Qualitative data were collected through in-depth interviews and observations to identify service problems, while quantitative data were obtained through a resident satisfaction questionnaire using a five-point Likert scale (n=100) as baseline data prior to system implementation. Results: The main problems in campus residential services were low responsiveness (mean=2,7) and reliability (mean=2,9), caused by non-integrated manual systems. A web-based digital residential service system was developed integrating residential administration, real-time complaint reporting, facility monitoring, and an operational dashboard for management. Functional testing shows that the system performs all main functions according to operational requirements. Novelty: The novelty of this study lies in evaluating an integrated digital campus residential service system from the perspective of educational support service management rather than solely from a technical information systems perspective.